2012
DOI: 10.1130/b30451.1
|View full text |Cite
|
Sign up to set email alerts
|

The effects of wildfire on the sediment yield of a coastal California watershed

Abstract: The occurrence of two wildfi res separated by 31 yr in the chaparral-dominated Arroyo Seco watershed (293 km 2) of California provides a unique opportunity to evaluate the effects of wildfi re on suspended-sediment yield. Here, we compile discharge and suspended-sediment sampling data from before and after the fi res and show that the effects of the postfi re responses differed markedly. The 1977 Marble Cone wildfi re was followed by an exceptionally wet winter, which resulted in concentrations and fl uxes of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
79
0
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(84 citation statements)
references
References 59 publications
4
79
0
1
Order By: Relevance
“…The provenance of storm waters above the lower Salinas was not a significant factor in determining CSSf for low to moderate flows, which indicates that upper basin wash load signals attenuate before reaching the lower Salinas stations. This is counterintuitive, as the Arroyo Seco and the upper Salinas are on average very different subbasins in terms of relief, area, vegetation and soil characteristics, and fire regimes (Farnsworth and Milliman, 2003;Warrick et al, 2012); and one would expect wash load signatures to differ, as more moderate differences in subbasin characteristics have been shown to cause significant differences in suspended sediment behavior (e.g., Ankers et al, 2003).…”
Section: U N C O R R E C T E D a C C E P T E Dmentioning
confidence: 82%
See 1 more Smart Citation
“…The provenance of storm waters above the lower Salinas was not a significant factor in determining CSSf for low to moderate flows, which indicates that upper basin wash load signals attenuate before reaching the lower Salinas stations. This is counterintuitive, as the Arroyo Seco and the upper Salinas are on average very different subbasins in terms of relief, area, vegetation and soil characteristics, and fire regimes (Farnsworth and Milliman, 2003;Warrick et al, 2012); and one would expect wash load signatures to differ, as more moderate differences in subbasin characteristics have been shown to cause significant differences in suspended sediment behavior (e.g., Ankers et al, 2003).…”
Section: U N C O R R E C T E D a C C E P T E Dmentioning
confidence: 82%
“…Transition to a primarily gravel bed occurs high in the upper Salinas, below the mainstem dam, while the Arroyo Seco transitions to a sand bed just before its confluence with the Salinas. Sediment export from the Arroyo Seco has been shown to be dominated by the convergence of wildfire and subsequent large 9 u n c o r r e c t e d , a c c e p t e d precipitation events (Warrick et al, 2012). The flashy nature of discharge in the Arroyo Seco leads to large flows produced rapidly relative to the upper Salinas, which can lead to lower Salinas discharge events that are primarily expressions of Arroyo Seco runoff.…”
Section: Study Region Characteristicsmentioning
confidence: 99%
“…However, these contaminants are released in more labile forms when vegetation and soil organic matter are burned and volatilized by fire (Young and Jan 1977;Biswas et al 2007;Wiedinmyer and Friedli 2007). In addition, wildfires increase erosion rates by as much as two orders of magnitude, which subsequently increases the transport rates of remobilized contaminants to water bodies (Cohen et al 2005;Stein et al 2012;Warrick et al 2012). While the impacts of wildfires on Hg influxes to aquatic systems have been relatively well documented (e.g., Kelly et al 2006), there is much less information on other trace elements (e.g., Pb and Zn) mobilized by wildfires (Erel et al 1997;Flegal 2011, 2014).…”
Section: Remobilization Of Trace Elements By Forest Firesmentioning
confidence: 99%
“…More recent studies have also incorporated temporal dependence in suspended sediment rating curves. Interannual to inter-decadal patterns of sediment behavior due to the effects of large flooding events (Kelsey, 1980;Klein and Anderson, 2012;Warrick et al 2013), wildfire (Shakesby and Doerr, 2006;Warrick et al, 2012) urbanization (Warick and Rubin, 2007) and combined land use changes (Pasternack et al, 2001) have all been shown to significantly affect decadal to inter-decadal scale suspended sediment flux.…”
Section: U N C O R R E C T E D a C C E P T E Dmentioning
confidence: 99%
“…Samples were collected by the authors as per Warrick et al (2012), with the following modifications. Samples were retrieved from the water surface at cross-channel stations of ~ onequarter, one-half, and three-quarters wetted channel width.…”
Section: Datamentioning
confidence: 99%